Developing trans-athlete policy in Australian National Sport Organizations. Issue 4 (2nd October 2021) - Stewart, L; O'Halloran, P; Oates, J; Sherry, E; Storr, R
ABSTRACT: The purpose of this study was to explore the way Australian national sport organisations (NSOs) create, develop and implement their policies relevant to trans athletes. Representatives of nine NSOs were interviewed utilising in-depth semi-structured interviews. Four key themes emerged from the organisation spokespersons' accounts: a) finding the right policy, b) underfunded and under resourced, c) challenges of educating employees and the public, and lastly, d) communication between NSOs and the trans athletic community. Findings revealed that only two NSOs reported had specific policies directed at trans athlete's sport participation. Several NSOs indicated that they had plans to develop separate policies for the different levels of competition to assist trans athletes to participate in their sport as their identified gender. This is the first study to explore the perspective and views of NSOs on the participation of trans athletes in sport.